2019
DOI: 10.1038/s41598-019-44386-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Aspirin Administration Has No Effect on Erectile Function: Evidence from Adult Rats and Ageing Rat Model

Abstract: As the broad spectrum pharmacological action, aspirin has been one of the most widely used medicines since its initial synthesis; however, the association between aspirin and erectile function is still controversial. We aim to explore whether long-term aspirin administration deteriorates or preserves erectile function from adult rats and ageing rat model. Twenty adult rats (10 weeks of age) and twenty ageing rats (80 weeks of age) were randomly divided into four groups as follows: Adult-Control (normal saline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…With a 1-week washout period after penile length measurement, erectile function was evaluated as previously described. 15 Briefly, after anesthesia induction, the isoflurane concentration was decreased and maintained at 2%. The carotid was exposed and can-…”
Section: Erectile Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…With a 1-week washout period after penile length measurement, erectile function was evaluated as previously described. 15 Briefly, after anesthesia induction, the isoflurane concentration was decreased and maintained at 2%. The carotid was exposed and can-…”
Section: Erectile Functionmentioning
confidence: 99%
“…The proximal penis stored with liquid nitrogen was homogenized, separated by SDS-PAGE, and transferred to a polyvinylidene difluoride membrane using standard procedures. 2,15 Primary antibody of LOX (1:1000, Abcam) was selected and normalized using glyceraldehyde-3-phosphate dehydrogenase (GAPDH; 1:200, Zen BioScience Co., Ltd.). Data were collected using the Bio-Rad ChemiDoc MP (Bio-Rad), and the band intensities were quantified using ImageJ software (National Institute of Health).…”
Section: Western Blotmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this meta-analysis shows strong evidence that using aspirin may significantly improve erectile function, there have been a few animal-based and human population-based and hospital-based studies that have suggested that aspirin may have no effect on or may increase the odds of ED (Kupelian et al, 2013;Li et al, 2019;Patel et al, 2016;Shiri et al, 2006). There were only two RCTs available for the meta-analysis.…”
Section: Discussionmentioning
confidence: 95%
“…Actually, old rats with ED always have a lower amount of NOS-containing nerves, as well as decreased NOS mRNA expression and NOS activity [ 40 , 58 ]. Our previous study also showed that aging rats had lower intracavernous pressure (ICP) and eNOS expression in the corpus cavernosum [ 59 ]. Additionally, rats with diabetes or bilateral cavernous nerve crush (BCNC) induced ED showed lower nNOS or eNOS expression and activity, as well as impaired NO production in the corpus cavernosum [ 39 , 40 , 60 , 61 ].…”
Section: Associations Between the Circadian Clock And Edmentioning
confidence: 99%